The association between interactive health literacy and dietary behaviors among Chinese college students: a large-scale cross-sectional study - Ma, Chunxiao; Ren, Zhongyu; Chen, Zhenqi; Li, Caifu (Frontiers in Psychology, 2024)
The association between health literacy and healthy dietary behaviors has been explored in the European population. However, there is currently no evidence available specifically pertaining to Chinese college students particularly for interactive health literacy.The objective of this study was to investigate the association between interactive health literacy (IHL) and dietary behaviors in Chinese college students.This study included 11,856 Chinese college students (mean age = 18.8 years, SD = 1.2 years). We defined nine healthy dietary behaviors as consumption of water, egg, milk and milk products, vegetables, fruit, red meat, soy and soy products, seafood, and sugar-sweetened beverages.We used the revised 28item Chinese Adolescent Interactive Health Literacy Questionnaire to evaluate IHL; a higher score on this scale indicates a greater health literacy. Multivariate logistic regression was used to analyze the association between IHL level and frequency of different numbers of dietary behaviors.After adjusting for sex, age, annual family income, place of residence, father's education level, and mother's education level, there was a clear and significant positive association between IHL and the likelihood of exhibiting diverse dietary behaviors. The adjusted odds ratio (95% CI) of exhibiting given nine dietary behaviors with reference to tertile 1 according to categories of IHL was as follows: 1.055 (0.694, 1.603) for tertile 2 and 1.849 (1.269, 2.696) for tertile 3 (p for trend = 0.001). Similarly, there are significant positive associations between IHL and the likelihood of exhibiting 2-8 dietary behaviors, except for exhibiting any one dietary behavior. We further found, in addition to the health awareness factor, there were significant positive associations between physical activity and nutrition factors, and healthier dietary behaviors. Further, there was a significant negative association between interpersonal relationships and dietary behavior.The findings indicate a positive relationship between IHL and dietary behavior, such that the higher the level of IHL among college students, the healthier the dietary behavior they tend to adopt in their daily lives. These findings suggest the importance of developing stages of changebased educational interventions, which could help individuals with limited IHL to not only acquire necessary health-related knowledge but also to strengthen their motivation to engage in healthy